Unveiling the nexus of the relationship between multiplayer digital game-playing experience and workplace loneliness: a moderated serial mediation analysis - Akgun, Ali E.; Keskin, Halit; Esen, Emel; Aksoy, Zeynep (SPRINGERNATURE, 2025)
BackgroundThe role of individuals' solo digital game-playing experience in influencing their feelings of loneliness is an important research area that has received considerable attention from researchers. However, we still know less about how the digital game-playing experience, in general, and the multiplayer digital game-playing experience, in particular, influence employees' loneliness in the workplace. In addition, although there are limited studies investigating the link between digital game playing and loneliness, the literature presents conflicting arguments and findings. Researchers have omitted various intervening psychological factors, such as boosting behavior and escapism motivation, as well as task characteristics, including task routineness, from the relationship between the multiplayer digital game-playing experience and loneliness.MethodThis study involved 120 employees from both service and manufacturing industries, representing a diverse range of ages, genders, and professional experiences, who participated in multiplayer digital gaming at work. Participants completed a self-report questionnaire measuring their multiplayer gaming experience, boosting behavior, feelings of workplace loneliness, self-expansion escapism, and the routine nature of their tasks. We employed a PLS-SEM approach using SmartPLS 4.0 to examine the relationships among these variables.ResultsOur study did not uncover a direct relationship between the experience of playing multiplayer digital games and feelings of loneliness. Instead, our findings revealed a significant serial mediation effect in the relationship between multiplayer digital game-playing experience and workplace loneliness, mediated explicitly through the enhancement of boosting behavior and self-expansion escapism. Our analysis indicated that (i) there exists a positive relationship between the experience of multiplayer digital game-playing and boosting behavior; (ii) boosting behavior is positively correlated with self-expansion escapism. Furthermore, we identified that self-expansion exhibits a negative relationship with workplace loneliness. Additionally, we observed that higher task routineness significantly attenuated the serial mediating relationship identified in our analysis.ConclusionThis study enhances the theoretical understanding of the importance of digital game play at work and offers practical implications for designing digital game activities to improve social relationships and reduce employee loneliness.
Keywords: Multiplayer digital game-playing experience; Boosting behavior; Loneliness; Self-expansion escapism; Task routineness; PSYCHOLOGY; MODELS; WORK